Benefits of Collaborating Finance Research in Business Schools - Robert Kao (Park University, 2012)
Collaboration in business research provides outcomes and results that are more efficient than those due to individual efforts. The integration of diverse environments and disciplines often generates creative ideas. Collaboration increases the quality of research and effectiveness of discoveries, and promotes the dissemination of knowledge. Cases of collaborative finance research in the business schools are illustrated in this study. The findings include many significant benefits in knowledge stimulation, education advancement, community connections, and other rewarding results. Benefits of collaborative research outweigh the challenges and contribute to faculty development, student education, and advancements in the field of business.